Recent progress of catalytic methane combustion over transition metal oxide catalysts - Gao, Yuan; Jiang, Mingxin; Yang, Liuqingqing; Li, Zhuo; Tian, Fei-Xiang; He, Yulian (Frontiers in Chemistry, 2022)
Methane is playing an increasingly indispensable role in our way to carbon neutrality, by providing less carbon-intensive heat and electricity worldwide. The atmospheric concentration of methane has raced past 1,900 ppb in 2021, almost triple its pre-industrial levels. As a greenhouse gas at least 86 times as potent as carbon dioxide over 20 years, methane is becoming a major threat to the global goal of deviating earth temperature from the +2 oC scenario. Consequently, all methane-powered facilities must be strictly coupled with remediation plans for unburned methane in the exhaust to avoid further exacerbating the environmental stress, among which, catalytic methane combustion (CMC) is one of the most effective strategies to solve this issue. Most current CMC catalysts are noble-metal-based owing to their outstanding C-H bond activation capability, while their high cost and poor thermal stability has driven the search for alternative options, among which, transition metal oxide (TMOs) catalysts have attracted extensive attention due to their earth abundance, high thermal stability, variable oxidation states, rich acidic and basic sites, etc. To date, many TMO catalysts have shown comparable catalytic performance with that of precious metals, while their fundamental reaction mechanisms are explored to a much less extent and remain to be controversial, which hinders the further optimization of the TMO catalytic systems. Therefore, in this review, we provide a systematic compilation of the recent research advances in TMO based CMC reactions, together with their detailed reaction mechanisms. We start with introducing the scientific fundamentals of CMC reaction itself as well as the unique and desirable features of TMOs applied in CMC, followed by a detailed introduction of four different kinetic reaction models proposed for the reactions. Next, we categorize the TMOs of interests into single and hybrid systems, summarizing their specific morphology characterization, catalytic performance, kinetic properties, with special emphasis on the reaction mechanisms and interfacial properties. Finally, we conclude the review with a summary and outlook on the TMOs for practical CMC applications. In addition, we also further prospect the enormous potentials of TMOs in producing value-added chemicals beyond combustion, such as direct partial oxidation to methanol.